2021
DOI: 10.1183/23120541.00429-2021
|View full text |Cite
|
Sign up to set email alerts
|

The risk of respiratory tract infections and antibiotic use in a general population and among people with asthma

Abstract: AimThe aim of this study was to investigate occupational, environmental, early life, and other risk factors associated with respiratory infections and antibiotics use, in a general population and among asthmatics.MethodThis study included 15 842 participants of the RHINE study aged 25–54 years from five Nordic countries, who answered a questionnaire covering respiratory outcomes, exposures, demographic characteristics and numbers of infections and courses of antibiotics the last 12 months. Multiple logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our finding of greater risk of respiratory adverse outcomes amongst people with active asthma compared to non-asthma is unsurprising and aligns with survey research from across the Nordic countries that found people with asthma reported substantially higher rates of LRTI and antibiotic use than people without. [19] Rates of asthma exacerbation amongst the active asthma cohort in our study were similar to previous studies from the CPRD. [20] To the best of our knowledge, no estimates exist for rates of asthma exacerbation or respiratory infection amongst a resolved asthma cohort.…”
Section: Comparison With Existing Literaturesupporting
confidence: 89%
“…Our finding of greater risk of respiratory adverse outcomes amongst people with active asthma compared to non-asthma is unsurprising and aligns with survey research from across the Nordic countries that found people with asthma reported substantially higher rates of LRTI and antibiotic use than people without. [19] Rates of asthma exacerbation amongst the active asthma cohort in our study were similar to previous studies from the CPRD. [20] To the best of our knowledge, no estimates exist for rates of asthma exacerbation or respiratory infection amongst a resolved asthma cohort.…”
Section: Comparison With Existing Literaturesupporting
confidence: 89%
“…In addition, nursing personnel, nurses, and doctors are at a higher risk of contracting non-specific RTIs compared to other hospital personnel [ 24 , 25 ], which is in alignment with our findings from a COVID-19 setting. Some other pre-COVID-19 pandemic reported RTI risk factors include sex [ 11 , 13 , 15 , 16 ], age [ 11 , 12 , 13 , 14 ], smoking [ 12 , 18 , 22 , 23 ], and chronic medical conditions [ 15 ] (diabetes mellitus [ 13 ], cardiovascular disease [ 13 ], and asthma [ 16 , 17 ]), which were included in our analysis but not found to be associated with non-specific symptomatic RTIs+COVID-19. A study conducted during the pandemic identified age, sex, chronic medical conditions (diabetes mellitus, hypertension, cardiovascular disease, and chronic kidney disease), immunosuppression, and obesity as risk factors for pneumonia [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the risk factors for the probability of contracting COVID-19 identified in previous studies include sex [ 4 , 5 , 6 , 7 , 8 ], age [ 6 , 7 , 8 , 9 ], higher body mass index (BMI) [ 4 , 6 , 8 ], higher glycated hemoglobin levels associated with diabetes [ 4 , 8 ], smoking [ 4 , 8 ], and use of blood pressure medications associated with hypertension [ 4 , 5 , 8 , 10 ]. Information about risk factors for the flu and other common respiratory diseases is available from government agencies like the Centers for Disease Control and Prevention (CDC) [ 2 ] and scientific research, where age [ 11 , 12 , 13 , 14 ], chronic medical conditions (chronic obstructive pulmonary disease (COPD) [ 15 ], diabetes mellitus [ 13 ], cardiovascular disease [ 13 ], asthma [ 16 , 17 ], obesity [ 11 , 12 , 18 , 19 , 20 , 21 ]), sex [ 11 , 13 , 15 , 16 ], smoking [ 12 , 18 , 22 , 23 ], being a part of the nursing personnel, a nurse, or a doctor [ 24 , 25 ], and others are identified as risk factors for RTIs, but it is unknown if the risk factors for RTIs before the COVID-19 pandemi...…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that clinicians use a lower dose of the drug for patients considered to be older and frailer. In addition, patients with asthma are at increased risk of infection [ 12 ], which may have influenced physicians’ dosing decisions regarding the use of baricitinib 2 mg. Patients in the bDMARD/tsDMARD-naive subgroup were more likely to be male and have a shorter RA duration, severe RA and higher C-reactive protein (CRP) levels than the bDMARD/tsDMARD-experienced subgroup, suggesting that clinicians are prescribing baricitinib before bDMARDs for selected patients, including males and patients with more severe RA.…”
Section: Discussionmentioning
confidence: 99%